Students' Perceptions of Using Google Classroom During Pandemic - Oktaria, Annafi Annanda; Rohmayadevi, Laksmita; Diniatulhaq, Rifdah; Farukh, Ammara (The Indonesian Institute of Science and Technology Research, 2024)
Technology has impacted most sectors, including the education field. Nowadays, many schools have incorporated technology by utilizing Information and Communication Technologies (ICT) into learning. Using platforms such as Google Classroom is one of the ways to fit the best classroom practices. This study reveals the student’s perception of using Google Classroom during the covid-19 pandemic. The method used in this research is descriptive qualitative through online questionnaires and deep interview sessions with students from SMP Muhammadiyah Yogyakarta. Twenty-eight students have been joining Google Classroom in English learning for at least one term during the COVID-19 pandemic. Findings showed that several factors influence the students' online learning process during a COVID-19 pandemic: usefulness, ease of use, ease of learning, and satisfaction. In general, Google Classroom is valuable and effective in improving students' skills, abilities, discipline, and independent learning through teaching materials.